Increased Public Legal Awareness of the Primary Rights of Road Users That Need to be Prioritized - Asep Suherman; Susi Ramadhani; Sudirman Sitepu (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The rampant violations of the main rights of road users that need to be prioritized can cause material and immaterial losses for those who get the main priority for road use. These violations can occur while driving or when utilizing road functions, due to intent, negligence, or ignorance. As a result of a lack of legal understanding and awareness, there is still a tendency to use and use roads not according to their designation, such as disruption of traffic order, delays for users of priority rights to obtain road access, and the potential for legal problems. The priority rights of road users that must be preceded are not fully understood by the community, especially regarding actions, criminal sanctions, and the importance of community participation. With this activity, people can add insight and knowledge to prevent and anticipate violations of the main rights of road users that need to be prioritized. The community is moved to orderly traffic to create conditions of obeying and obeying the law. As well as being able to provide awareness and increase legal awareness to prevent traffic violations in the future.